Hybridization Effect on Crashworthiness Parameters of Natural Composite - Salim Hamza, Sabah; Ismail, Al Emran; Yuhazri, M. Y.; Ariffin, Ahmad Hamdan; Hameed Sultan, Mohamed Thariq (Frontiers in Materials, 2021)
The use of metallic materials in automotive industry leads to increasing fuel consumption and cost, so trends are starting to use lighter and cheaper materials. In automotive applications, fibers are used in composites because they are stronger, stiffer, and lighter than bulk materials, and they can achieve higher energy absorbing compared to metallic materials. The purpose of this work is to study the potential utilization of natural fibers in the crash energy absorbing applications. The experimental procedures (the principle of a combination of manual layup and vacuum bladder technique) were applied to search the influence of utilizing jute fiber mat on crashworthiness parameters of composite materials with other kinds of fibers such as woven glass fiber reinforced epoxy composites. The study involved corrugated composite tubes with three layers of jute and hybrid glass-jute/epoxy material have been tested in uniaxial quasi-static crush conditions at the speed 10 mm/min. The results exhibit that the tube of jute fiber was somewhat lower than synthetic fibers, but the substitution of one layer of jute fiber with one layer of glass fiber resulted in an improvement in the crashworthiness parameters. As hybrid jute-glass was used, the best result was obtained, where energy absorption and specific energy absorption are improved by 17.75% and 25.122%, respectively.